Intermediate Electrostatic Field for the Generalized Elongation Method. Issue 7 (12th March 2015) - Liu, Kai; Korchowiec, Jacek; Aoki, Yuriko
Abstract An intermediate electrostatic field is introduced to improve the accuracy of fragment‐based quantum‐chemical computational methods by including long‐range polarizations of biomolecules. The point charge distribution of the intermediate field is generated by a charge sensitivity analysis that is parameterized for five different population analyses, namely, atoms‐in‐molecules, Hirshfeld, Mulliken, natural orbital, and Voronoi population analysis. Two model systems are chosen to demonstrate the performance of the generalized elongation method (ELG) combined with the intermediate electrostatic field. The calculations are performed for the STO‐3G, 6‐31G, and 6‐31G(d) basis sets and compared with reference Hartree–Fock calculations. It is shown that the error in the total energy is reduced by one order of magnitude, independently of the population analyses used. This demonstrates the importance of long‐range polarization in electronic‐structure calculations by fragmentation techniques.